2014
DOI: 10.1371/journal.pone.0097230
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and Plasma Level of Transforming Growth Factor-Beta 1 and Risk for Preeclampsia: A Systematic Review

Abstract: BackgroundTransforming growth factor-beta 1 (TGF-β1) is thought to be involved in the pathogenesis of preeclampsia (PE), but the results are inconsistent among studies. This article aims to compile an overview of the studies about the associations of TGF-β 1 polymorphism and plasma level with PE risk and to provide recommendations for future research.Methods and ResultsThe databases PubMed, Embase and Web of Science were searched up to December 2013. Five studies investigating the associations of four polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 65 publications
0
26
0
1
Order By: Relevance
“…Keeping this in consideration, preceding studies attempted to examine any possible alterations of maternal TGF-b1 plasma levels in pre-eclamptic women. The results of some of these studies demonstrated elevated TGF-b1 concentrations in women with PE as compared to normotensive pregnant women, indicating that TGF-b1 synthesis and secretion might be dysregulated in PE pregnancies [18,20,21]. Additionally, some previous reports revealed altered levels of serum TGF-b1 based on the stage of pregnancy [18,21].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Keeping this in consideration, preceding studies attempted to examine any possible alterations of maternal TGF-b1 plasma levels in pre-eclamptic women. The results of some of these studies demonstrated elevated TGF-b1 concentrations in women with PE as compared to normotensive pregnant women, indicating that TGF-b1 synthesis and secretion might be dysregulated in PE pregnancies [18,20,21]. Additionally, some previous reports revealed altered levels of serum TGF-b1 based on the stage of pregnancy [18,21].…”
Section: Introductionmentioning
confidence: 92%
“…It is a 25-KDa homodimeric protein and is believed to control proliferation and differentiation of several cell types including foetal cytotrophoblasts and regulation of trophoblast invasion [16,17]. TGF-b1 has been shown to influence embryonic growth and development, apoptosis of endothelial cells and has recently been proposed to be one of the candidate genes for PE [18]. More importantly, this gene is considered as one of the master regulators for monitoring the number of the FOXP3 + regulatory T cells (Tregs), which play a crucial role in the maintenance of selftolerance, physiological immune responses and also mediate maternal tolerance to the foetus.…”
mentioning
confidence: 99%
“…Two current publications dealing with populations of varying ethnicities, point out towards reduced levels of TGF-β1 in the second trimester of pregnancy and increased levels during the third trimester and post-delivery in PE women, whereas the scenario is reported to be opposite in normal pregnancies [32,33] (Figure 1a). In the light of the existing literature and based on the functional significance of the SNPs studied, Goske et al, argue that the intermediary levels associated with heterozygous genotype confer a selective advantage and might protect women from PE, though their study did not involve measurement of serum TGF-β1 levels [22,23].…”
Section: Polymorphic Variants Of Tgfb1 Gene and Serum Levels Of Tgf-βmentioning
confidence: 97%
“…It also influences embryonic growth, development as well as apoptosis of endothelial cells. Fundamentally, this gene is considered as one of the master regulators for monitoring the number ofFOXP3+ regulatory T cells [Tregs], which play a crucial role in the maintenance of selftolerance, physiological immune responses and moreover mediates maternal tolerance to the paternal antigens of the foetus [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…(8) Meanwhile, another study showed that TGF-β1 was significantly lower in the preeclamptic group than in normal pregnancy. (9) In another side, Enquobahrie, et al, reported that Zimbabwe women with preeclampsia tend to have a higher TGF-β1 than normal pregnant women. 10The possibility of TGF-β1 as a marker for preeclampsia and the inconsistent results which were found in the previous studies have intrigued the writers to study the differences in mean serum levels of TGF-β1 in the preeclamptic patients and normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%